The USP19 Deubiquitinase Regulates the Stability of c-IAP1 and c-IAP2 - Mei, Yide (American Society for Biochemistry and Molecular Biology, 2011)
The inhibitors of apoptosis (IAPs) are critical regulators of apoptosis and other fundamental cellular processes. Many IAPs are RING domain-containing ubiquitin E3 ligases that control the stability of their interacting proteins. However, how IAP stability is regulated remains unclear. Here we report that USP19, a deubiquitinating enzyme, interacts with cellular IAP 1 (c-IAP1) and c-IAP2. Knockdown of USP19 decreases levels of both c-IAPs, whereas overexpression of USP19 results in a marked increase in c-IAP levels. USP19 effectively removes ubiquitin from c-IAPs in vitro, but it stabilizes c-IAPs in vivo mainly through deubiquitinase-independent mechanisms. The deubiquitinase activity is involved in the stabilization of USP19 itself, which is facilitated by USP19 self-association. Functionally, knockdown of USP19 enhances TNFα-induced caspase activation and apoptosis in a c-IAP1 and 2-dependent manner. These results suggest that the self-ubiquitin ligase activity of c-IAPs is inhibited by USP19 and implicate deubiquitinating enzymes in the regulation of IAP stability.